Given that \( f(x)=(x-4)^{2} \) and \( g(x)=1-5 x \), find (a) \( (f+g)(-4)=\square \) (b) \( (f-g)(-4)=\square \) (c) \( (f g)(-4)=\square \) (d) \( \left(\frac{f}{g}\right)(-4)=\square \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve the given expressions, we first need to evaluate \( f(-4) \) and \( g(-4) \). 1. Calculate \( f(-4) \): \[ f(-4) = (-4 - 4)^2 = (-8)^2 = 64 \] 2. Calculate \( g(-4) \): \[ g(-4) = 1 - 5(-4) = 1 + 20 = 21 \] Now we can find the required expressions: (a) \( (f+g)(-4) \): \[ (f+g)(-4) = f(-4) + g(-4) = 64 + 21 = 85 \] (b) \( (f-g)(-4) \): \[ (f-g)(-4) = f(-4) - g(-4) = 64 - 21 = 43 \] (c) \( (fg)(-4) \): \[ (fg)(-4) = f(-4) \cdot g(-4) = 64 \cdot 21 = 1344 \] (d) \( \left(\frac{f}{g}\right)(-4) \): \[ \left(\frac{f}{g}\right)(-4) = \frac{f(-4)}{g(-4)} = \frac{64}{21} \] Now we compile the results: (a) \( (f+g)(-4) = 85 \) (b) \( (f-g)(-4) = 43 \) (c) \( (fg)(-4) = 1344 \) (d) \( \left(\frac{f}{g}\right)(-4) = \frac{64}{21} \)